Design Of An Educational Game For Numbers In Early Childhood With Android-Based Biometrics - Septiardi, Rizqy Dwi; Wahana, Aditya; Rianto (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2024)
Counting is learning from mathematics logical and ability sorting , counting and thinking in a way logical . Skills count very required in life everyday . Counting is also a​ skills base mathematics in Education . Purpose of Counting is For learn basics​​ mathematics so that child Ready face learning more counting​ complex.media Conventional which is often used teacher in give lesson counting to child not enough effective due to the development of the electronic world at that time this . Therefore That Making a Counting Game This aiming For follow development of the times with develop a counting game that can used on android with use method biometrics as learning.Based on Trial the system that has been carried out by media experts and expert material get results like following 80% or very worthy by media experts and 75% or qualified by expert material . Testing Application This No only carried out by media experts and expert material just testing​ also conducted on students at KB TK AN NAHL. Test Results to 20 students of KB TK AN NAHL received results like following 85% very agree and agree , 14% less agree and 1% disagree agree using this game.